FACTORS INFLUENCING HEALTH SEEKING BEHAVIOUR AMONG RESIDENTS OF BASAWA COMMUNITY, SABON GARI L.G.A. KADUNA STATE, NIGERIA - Usman NO; Ibrahim MJ; Joshua IA; Muhammad-Idris ZK; Zubairu HD (Ntec Specialist, 2020)
Background: The health of the citizenry is crucial to the growth and development of any nation. Nigeria is riddled with poor health indices ranging from maternal mortality to infant mortality rates. It has been established that health-seeking behaviour has a strong influence on health status, morbidity and mortality indices of a society. It also drives utilisation of health services and is affected by predisposing, enabling and need factors. This study assessed the factors influencing health-seeking behaviour among residents of Basawa community, Sabon Gari LGA, Kaduna State, Nigeria. Method: This was a descriptive cross-sectional study carried out in September 2017 among 125 residents of Basawa community selected by systematic sampling technique. Data was collected using a semi-structured interviewer-administered questionnaire and analysed with SPSS version 21. The results were presented as tables and charts among others. Level of statistical significance was set at p less than 0.05. Results: The mean age of the respondents was 42±10 years. Majority of the respondents were male (60.8%) and married (90.4%). About two-thirds of the respondents delayed for more than 24 hours before seeking healthcare. Long waiting time (55.2%), the attitude of health workers (22.4%) and the high cost of drugs (22.4%) were given as barriers to health care utilisation. High cost of services, type and severity of illness and attitude of health care workers are the main determinants of health-seeking behaviour. There was a statistically significant relationship between education, monthly income and delay in seeking health care. Conclusion: The study showed several factors that influence health care seeking behaviour. In view of the multifactorial determinants of health-care seeking behaviour, there is need for health workers to be trained and retrained to improve on their attitude, and the provision of community-based social health insurance scheme by the government among others.